2021
DOI: 10.3126/jnapd.v2i1.41596
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Prevalence among 3 - 14 Year Old School Children of Chitwan

Abstract: Introduction: Dental caries, an infectious microbiologic disease of dental hard tissues is a global public health problem. It affects people of all ages with the highest priority risk group being school-going children. Objective: This study was done to assess the prevalence of dental caries in the 3-14 years old school children of Chitwan and to compare it across genders, age groups and school groups. Methods: This was a cross-sectional study conducted from January 2018 to May 2018 where WHO criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…8 This prevalence is also higher than the desired dental caries prevalence stated in the National oral health policy of Nepal. 9 Similar high prevalence rates were reported by Adhikari et al, 10 Type of schools were evaluated for dental caries status to see for possible changes. The present study showed that there is no significant differences among the caries status.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…8 This prevalence is also higher than the desired dental caries prevalence stated in the National oral health policy of Nepal. 9 Similar high prevalence rates were reported by Adhikari et al, 10 Type of schools were evaluated for dental caries status to see for possible changes. The present study showed that there is no significant differences among the caries status.…”
Section: Discussionmentioning
confidence: 58%
“…School going children of age 3-15 years were selected for the study. A study conducted by Adhikari et al 10 showed the prevalence dental caries as 63.83%. By considering this as a prevalence with 95% confidence interval, with 5% margin of error, sample size was determined based on the formula, n=z 2 pq/e 2 , were, Z= 1.96 for 95% confidence interval.…”
Section: Methodsmentioning
confidence: 97%
“…Dhar et al 4 , Garkoti et al 27 , Joshi et al 20 , Shitie A et al 21 and Wang Z et al 28 reported in their studies that caries prevalence was higheramong the boys than girls(66.91% and 59.03%; 60% and 56%; 80% and 73%; 57.7% and31.8%; 51.53% and 48.46% respectively). While contrastingly, a few studies by Rajesh et al 11 , Ahmed et al 15 , Sultana S et al 22 and Adhikari S et al 23 showed the dental caries prevalence was almost equal among the female and male students (34% and 31.8%; 30.7% and 31%; 81.8% and 83.8%; 86.48% and 85.14% respectively).…”
Section: Discussionmentioning
confidence: 92%
“…[5][6][7] However, in the context of Nepal, most studies regarding the prevalence of caries have been conducted among only children and adolescents. [8][9][10][11][12][13] A comprehensive insight into prevalence rates of dental caries among the adult population based on the type of dental caries has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%